State Sovereignty And Mining Concessions In Peru (Journal of Namibian Studies : History Politics Culture, 2023)
The State and sovereignty is a composite concept of high significance in the role played by the State in the use, exploitation and guarantee of the well-being of the inhabitants within its territory. This term, born in the modern age, is associated with various sociocultural, economic and political events, and is composed of certain elements, such as territory (resource), people (population), power (government) and sovereignty (rights), the latter understood as the power that the people cede to a government or authorities. The internal recognition of a delimited territory and the external distinction of other States, it can be said that it is not exclusive to the Nation-State, but also becomes an expression of the legal-political order of the same peoples that make up the State, thus maintaining a double discourse with slight nuances in the definition of power at the local (traditional) level. The analysis of this term is very important and complex, since sovereignty gives the State the ability to directly dispose of and manage its resources. In this sense, the objective of this research is to understand the theoretical definition of the role of the State and the exercise of its sovereignty in relation to mining concessions in Peru. The research uses a mixed descriptive, non-experimental method, which was carried out through bibliographic analysis and statistical interpretation generated by state institutions, using the SPSS statistical package for this analysis. The results obtained